(untitled) (Swiss Medical Weekly, 2025)
STUDY AIMS: A history of gestational diabetes mellitus is a known risk factor for developing type 2 diabetes in the future. Therefore, screening for persistent dysglycaemia in the postpartum period is of utmost importance. However, follow-up rates tend to be low. The aim of this study was to investigate postpartum screening adherence at a tertiary care centre and to identify factors contributing to persistent dysglycaemia. METHODS: A cohort of women with gestational diabetes mellitus diagnosed between 2015 and 2018 at the department of Obstetrics and Gynaecology, University Hospital Bern, Switzerland, was retrospectively studied. Ethnicity, parity, pre-pregnancy BMI, family history of diabetes mellitus, first trimester glycosylated haemoglobin (HbA1c), 75 g oral glucose tolerance test during pregnancy and in the postpartum period were analysed. Postpartum dysglycaemia was defined as overt diabetes (fasting plasma glucose ≥7.0 mmol/l and/or 2 hours plasma glucose ≥11.1 mmol/l for the 75 g oral glucose tolerance test), impaired glucose tolerance (2 hours plasma glucose 7.8–11.0 mmol/l) or impaired fasting glucose (plasma glucose 5.6–6.9 mmol/l). Parametric and non-parametric tests as well as multivariate regression were used. ROC analyses were performed to assess the prognostic accuracy of HbA1c and oral glucose tolerance test results at predicting postpartum dysglycaemia. RESULTS: We included 489 women with gestational diabetes mellitus in our study. Of these, 217 (44.4%) returned for postpartum testing and 59/217 (27.2%) had an abnormal oral glucose tolerance test. Ethnicity was found to be a factor in adherence to follow-up. Specifically, women of African origin showed a significantly higher compliance than Asian or Caucasian women (61.8% vs 47.8% vs 34.5%, respectively; p = 0.04). The multivariate analysis revealed that obesity (OR: 3.64, 95% CI: 1.41–9.37) and first trimester HbA1c >5.7% (OR: 3.67, 95% CI: 1.28–10.52) are significantly associated with an increased risk of postpartum dysglycaemia. CONCLUSION: Our study indicates that adherence to postpartum screening after gestational diabetes mellitus is low but in line with the existing experience. This is of particular concern as 1 of 4 women undergoing postpartum screening show some sort of disturbed glucose metabolism. In particular, women with higher first trimester HbA1c and/or obesity may warrant closer observation and motivation for testing as the risk for persistent metabolic disorders is increased.